1996
DOI: 10.1080/10807039609383629
|View full text |Cite
|
Sign up to set email alerts
|

An approach for estimating ecological risks from organochlorine pesticides to terrestrial organisms at rocky mountain arsenal

Abstract: Ecological risk assessment for bioaccumulative chemicals at hazardous waste sites like Rocky Mountain Arsenal (RMA) is challenging, particularly when the site is large and is characterized by heterogeneous environments and patterns of contamination. Because RMA is an National Priorities List site and a future wildlife refuge, an effective and practical risk assessment approach was required. This approach includes methods to estimate contaminant concentrations below detection limits, spatial and temporal integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Several studies ( ) have indicated that the relative spatial positions of receptors and contaminated media can strongly influence estimates of exposure and hence of risk. Inclusion of the spatial relationship of receptors, their habitats, and contaminants can result in more representative, and possibly more ecologically relevant, risk assessments ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies ( ) have indicated that the relative spatial positions of receptors and contaminated media can strongly influence estimates of exposure and hence of risk. Inclusion of the spatial relationship of receptors, their habitats, and contaminants can result in more representative, and possibly more ecologically relevant, risk assessments ( ).…”
Section: Introductionmentioning
confidence: 99%
“…However, dieldrin levels in birds and mammals were adequately predicted by a model that incorporated distributions of tissue:soil BAFs derived from site-specific data [12]. Likewise, estimates of mercury and polychlorinated biphenyl residues in great blue heron (Ardea herodias) eggs made with a stochastic food web model were in reasonable agreement with concentrations measured in a limited number of egg samples [7].…”
Section: Introductionmentioning
confidence: 54%
“…Menzie et al [11] modeled DDT residues in birds and small mammals with tissue:food bioaccumulation factors, but predictions were plagued by large uncertainties, and validation was limited by small sample sizes. However, dieldrin levels in birds and mammals were adequately predicted by a model that incorporated distributions of tissue:soil BAFs derived from site-specific data [12]. Likewise, estimates of mercury and polychlorinated biphenyl residues in great blue heron (Ardea herodias) eggs made with a stochastic food web model were in reasonable agreement with concentrations measured in a limited number of egg samples [7].…”
Section: Introductionmentioning
confidence: 57%
“…This model includes stochasticity in pollutant effects, sublethal end points, exposure estimates, and pesticide fate discriminated on the basis of landscape structure and time‐scaled treatment of pollutant fate and persistence within exposed biota. Examples of geographic information system approaches using data on real landscapes and population behavior have also been presented [87–89].…”
Section: Metapopulationsmentioning
confidence: 99%